MUNICIPAL FINANCE IN KERALA :COMPOSITION AND TRENDS IN REVENUE RECEIPTS OF CORPORATIONS - Thomas, Anitha; Kuriakose, Sony (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Municipal corporations in Kerala, play a crucial role in providing essential public services to citizens. However, their financial sustainability is a concern due to inadequate revenue, inefficient expenditure management, and poor governance. This study examines the composition and trends in revenue receipts of municipal corporations in Kerala, with a focus on identifying the key sources of revenue, trends, and patterns. The study uses a descriptive and analytical approach, combining data from secondary sources, including annual reports and financial statements of municipal corporations, with primary data collected through surveys and interviews with municipal officials. The findings reveal that tax revenue is the primary source of revenue for municipal corporations in Kerala, followed by non-tax revenue and grants-in-aid. The study also identifies significant trends and patterns in revenue receipts, including an increasing reliance on non-tax revenue sources and a decline in the share of tax revenue. The study’s findings have implications for policymakers, practitioners, and researchers seeking to improve the financial sustainability of municipal corporations in Kerala.